Chronic Pain and Analgesic Use in CKD: Implications for Patient Safety - Wu, Juliana (Clin J Am Soc Nephrol, 2015)
BACKGROUND AND OBJECTIVES: Chronic pain in predialysis CKD is not fully understood. This study examined chronic pain in CKD and its relationship with analgesic usage. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: Data include baseline visits from 308 patients with CKD enrolled between 2011 and 2013 in the Safe Kidney Care cohort study in Baltimore, Maryland. The Wong–Baker FACES Pain Rating Scale measured chronic pain severity. Analgesic prescriptions and over-the-counter purchases were recorded up to 30 days before visits, and were classified as a drug-related problem (DRP) based on an analgesic’s nephrotoxicity and dose appropriateness at participants’ eGFR. Participants were sorted by pain frequency and severity and categorized into ordinal groups. Analgesic use and the rate of analgesics with a DRP were reported across pain groups. Multivariate regression determined the factors associated with chronic pain and assessed the relationship between chronic pain and analgesic usage. RESULTS: There were 187 (60.7%) participants who reported chronic pain. Factors associated with pain severity included arthritis, taking ≥12 medications, and lower physical function. Use of nonsteroidal anti-inflammatory drugs was reported by seven participants (5.8%) with no chronic pain. Mild and severe chronic pain were associated with analgesics with a DRP, with odds ratios of 3.04 (95% confidence interval [95% CI], 1.12 to 8.29) and 5.46 (95% CI, 1.85 to 16.10), respectively. The adjusted rate of analgesics with a DRP per participant increased from the group with none to severe chronic pain, with rates of 0.07 (95% CI, 0.04 to 0.13), 0.12 (95% CI, 0.07 to 0.20) and 0.16 (95% CI, 0.09 to 0.27), respectively. CONCLUSIONS: Chronic pain is common in CKD with a significant relationship between the severity of pain and both proper and improper analgesic usage. Screening for chronic pain may help in understanding the role of DRPs in the delivery of safe CKD care.